(untitled) (The Voz a Vos Bulletin, 2022)
Tushuna was a dance meeting held on June 18, 2022, in Quito Ecuador in the cultural exchange between the Colombian Performing Artist Gigi-Ingrid Terreros and the Corazón de Fuego Cultural Space, Nina Shunk. The objective of this experience was to investigate how we experience dance from Latin America and how in intercultural dialogue it was possible to rethink, feel and create a dance from the awareness of the territory we inhabit. This work, methodologically, is a return to that meeting to reflect on how creativity in the artistic field is conjunctural to the sociocultural field and how from the dialogue between experience and critical interculturality it is possible to propose a situated knowledge that proposes findings, possible paths. . and questions the artistic and investigative practice itself. The epistemic position as a political position of critical interculturality and decolonial thought is TUSHUNA.